ON SEMIPRIME SUBSEMIMODULES AND RELATED RESULTS - Hamid Agha Tavallaee; Masoud Zolfaghari (Journal of the Indonesian Mathematical Society, 2013)
In this paper we introduce the notions of semiprime subsemimodules and semiprime k-subsemimodules and present some characterizations about them. Special attention has been paid, when semimodules are multiplication, to find extra properties of these semimodules. Moreover we prove a result for semiprime subsemimodules of quotient semimodules.DOI : http://dx.doi.org/10.22342/jims.19.1.129.49-59